LncRNA GAS5/miR-137 Is a Hypoxia-Responsive Axis Involved in Cardiac Arrest and Cardiopulmonary Cerebral Resuscitation - Jing, Wang; Tuxiu, Xie; Xiaobing, Long; Guijun, Jiang; Lulu, Kang; Jie, Jiang; Lu, Ye; Liying, Zhan; Xiaoxing, Xiong; Jingjun, Lyu (Frontiers in Immunology, 2022)
Background: Cardiac arrest represents one of the devastating medical emergency and is assoiciated with high mortality and neuro-disability. Post-cardiac arrest syndrome is mechanistically ascribed to acute systemic ischemia/ reperfusion injury. The lncRNA/microRNA/mRNA have been found to play crucial roles in the pathogenesis of the hypoxia-responsive diseases. Nonetheless, the precise mechanisms by which lncRNA/miRNA/mRNA axes in CA/CPR have not been fully elucidated. Methods: We collected and purified the exosomes from the blood of CA/CPR patients and supernatant of OGD/R-stimulated astrocytes. On the basis of microarray analysis, bioinformatic study , we speculated that LncRNA GAS5/miR-137/ INPP4B is implicated in the astrocyte-microglia crosstalk under the insult of systemic ischemia-reperfusion injury. The regulation of lncRNA GAS5/miR-137 on INPP4B was examined by cellular transfection in OGD/R model and by lateral ventricle injection with miR-137 agomir in CA/CPR mice model. Flowcytometry and staining were performed to detect the microglial apoptosis, M1/M2 phenotype transformation, and neuroinflammation. Neurological scoring and behavior tests were conducted in CA/CPR group, with miR-137 agomir lateral-ventricle infusion and in their controls. Results: miR-137 was among the top 10 micRNAs that experienced greatest changes, in both the blood of CA/CPR patients and supernatant of OGD/R-stimulated astrocytes. Bioinformatic analysis revealed that miR-137 was sponged by LncRNA GAS5, targeting INPP4B, and the result was confirmed by Luciferase activity assay. qRT-PCR and Western blotting showed that LncRNA GAS5 and INPP4B were over-expressed whereas miR-137 was down-regulated in the blood of CA/CPR patients, OGD/R-stimulated astrocytes, and brain tissue of CA/CPR mice. Western blotting exhibited that INPP4B expression was suppressed and phosphorylation of PI3K/Akt was increased when LncRNA GAS5 was silenced or miR-137 was over-expressed. However, PI3K/Akt phosphorylation was notably suppressed in the absence of miR-137, almost reversed their phosphorylation in the silencing LncRNA GAS5 group. Then we found that LncRNA GAS5 siRNA or miR-137 mimic significantly increased cell viability and alleviated apoptosis after OGD/R. Furthermore, over-expression of miR-137 attenuated microglial apoptosis and neuroinflammation in CA/CPR mice model, exhibiting significantly better behavioral tests. Conclusion : LncRNA GAS5/miR-137 may be involved in the astrocyte-microglia communication that inhibits PI3K/Akt signaling activation via regulation of INPP4B during CA/CPR.